STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART, AND MATHEMATICS) EDUCATION AND TEACHERS’ PEDAGOGICAL DISCONTENTMENT LEVELS - Thompson, Carla J; Barber, Karen; Bourget, Ernest M (PEOPLE: International Journal of Social Sciences, 2018)
Literature focused on the emerging implementation of STEAM (Science, Technology, Engineering, Art, and Mathematics) education within K-12 education programs in the USA emphasizes the need for researchers to address the potential for disrupting the pedagogical contentment of teachers assigned to teach in STEAM disciplines who have no backgrounds in the fields represented by STEAM and/or who have no prior teaching experience in the areas of STEAM. Research objectives for the current study focused on examining the influence of intensive professional development on K-12 teachers’ pedagogical discontentment levels relative to the implementation of STEAM in all classrooms within a rural school district in the southeast region of the United States. Data sources included: (a) pre-post assessments of 93 teachers’ pedagogical discontentment levels; (b) classroom observation data collected by external observers; and (c) teachers’ perceptions of STEAM coaching. Data retrieved were analyzed using quantitative analyses. Study findings indicated teachers’ pedagogical discontentment levels decreased over time. Future research must support teachers new to STEAM activities.